Understanding why and how youth-friendly health services improve viral load suppression among adolescents and young people living with HIV in Nigeria: realist evaluation with qualitative comparative analysis - Okikiolu Badejo; Prosper Okonkwo; Edwin Wouters; Sara Van Belle; Christiana Nöstlinger; Marie Laga; Plang Jwanle (BMJ Global Health)
Introduction Youth-friendly health service (YFHS) approaches are essential to better outcomes for young people. We evaluated attainment of viral load suppression among young people living with HIV (YPLHIV) enrolled in an HIV treatment programme implementing YFHS models in Nigeria.Methods A realist evaluation using qualitative and quantitative programme data from 10 implementing health facilities. We used qualitative information to explore how and why viral load suppression was attained across different settings and quantitative data to describe patterns and associations between youth-friendly structures and processes of care, care retention and viral load suppression. To consolidate the theories, we used qualitative comparative analysis to identify the necessary and sufficient conditions for attaining viral load suppression, using 30 YPLHIV as cases.Results Between baseline (2018) and study-end (May 2022), viral load suppression coverage increased in 8 of the 10 study facilities. The number of facilities with viral load suppression coverage ≥90% rose from two to seven, while one facility remained unchanged, and another had a decline in coverage. Among the 30 selected YPLHIV cases, 18 had viral load suppression during the first test and 24 at the second test. However, viral load suppression attainment varied in different contexts. We identified the different YFHS interventions and key mechanisms that influenced viral load suppression in different contexts.Conclusion YFHS interventions can improve young people’s engagement with HIV services, but their effectiveness depends on specific mechanisms and contextual factors influencing their response to interventions. By exploring how and why viral load suppression was attained in different contexts, the findings will improve the design and implementation of strategies to improve outcomes in young people, which will be relevant for achievement of global goals to eliminate HIV by 2030.